Konsistensi Sistem Prakiraan Iklim Musiman Menggunakan Indikator ENSO di Daerah Tipe Iklim D3 dan D4 Kabupaten Lombok Tengah - Lara Miga Wahyuni; Fahrudin Fahrudin; Mahrup Mahrup (Journal of Soil Quality and Management, 2023)
The purpose of this study was to determine the consistency of seasonal climate forecasts using the ENSO phenomenon. The ENSO indicator categorized with El Nini, Neutral and La Nina were coorelated to rainfall categorized with Below Normal, normal and above normal. The research was carried out in the D3 dan D4 type of climate in ccentral Lombok regency.  The method used in this research is descriptive method, which is a method aimed at solving problems by collecting data, compiling, analyzing, interpreting data, and drawing conclusions. This research was conducted in Central Lombok in climate types D3 and D4 covering the areas of Kopang, Mantang, Praya, Puyung, Pringgarata, Penujak, Mujur, Pujut, and Janapria. Using monthly rainfall data for ± 50 years from 1970-2019. Rainfall data were taken at Kopang, Mantang, Praya, Puyung, Pringgarata stations for type D3 and Penujak, Mujur, Pujut, and Janapriafor type D4. SOI data can be accessed at http://www.bom.gov.au/climate/current/soi2.shtml. The results showed that from 1970-2019 (50 years) there was a consistent value in all areas that were predicted, namely above 50% and inconsistency below 50%. Consistency describes how accurate the results of the forecast are. If the percentage of the consistency value is above 50%, it means that it is better to predict using the forecasting method by looking for consistency than using the average. Therefore, if you use a forecasting system, if an El Nino phenomenon occurs there will be a shortage of water, you can adjust the planting time, prepare irrigation water first, reduce the planting area, and delay the planting time first.Keywords: Climate Variations, SOI, Rainfall, Climate D3 and D4